Collective self-fulfilling prophecies: group identification biases perceptions of environmental group norms among high identifiers. (2nd July 2016) - Masson, Torsten; Jugert, Philipp; Fritsche, Immo
Abstract: Previous research has shown that ingroup norms influence intentions to engage in pro-environmental behavior, most notably for individuals highly identified with a group. However, intriguingly, identification may itself lead people to exaggerate descriptive pro-environmental ingroup norms to enhance positive distinctiveness of their ingroup. We investigated this possibility in two studies together with the assumption that perceived norms would mediate the effects of identification on intentions to engage in pro-environmental behavior. The results support our assumptions and show that high identifiers perceived their ingroup be more eco-friendly, which in turn increased respondents' intentions to behave in a pro-environmental manner. We discuss the implications of this collective self-fulfilling prophecy for social identity theorizing and the prediction of pro-environmental behavior.